2022
DOI: 10.1007/s12325-022-02140-2
|View full text |Cite
|
Sign up to set email alerts
|

Enzalutamide in Chemotherapy-Naïve Metastatic Castration-Resistant Prostate Cancer: An Asian Multiregional, Randomized Study

Abstract: Introduction Enzalutamide significantly improved clinical outcomes compared with placebo in patients with chemotherapy-naïve metastatic castration-resistant prostate cancer (mCRPC) with disease progression despite androgen deprivation therapy (ADT) in the PREVAIL study. However, few patients from Asia were enrolled. Our study (NCT02294461) aimed to evaluate the safety and efficacy of enzalutamide in this disease setting in patients in mainland China, Korea, Taiwan, and Hong Kong. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The analysis included seven multicenter RCTs, predominantly phase III first-line treatments, with the exception of one phase IV second-line treatment RCT included for network completeness ( 10 16 ). These trials spanned 2015 to 2020, involving a total of 6,411 participants.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis included seven multicenter RCTs, predominantly phase III first-line treatments, with the exception of one phase IV second-line treatment RCT included for network completeness ( 10 16 ). These trials spanned 2015 to 2020, involving a total of 6,411 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Data from 24 eligible RCTs (n = 22 166) were included (Figure 1); M0 HSPC (3 RCTs, n = 2171), M1 HSPC (9 RCTs, n = 8994), M0 CRPC (3 RCTs, n = 4256), M1 CRPC (9 RCTs, n = 6745) . One study had patients spanning different disease states, so these populations were split for analysis according to their separate publications .…”
Section: Resultsmentioning
confidence: 99%
“…Studies investigated SOC used with ARSI monotherapy or combined with another ARSI or docetaxel. The following agents were combined with SOC therapy: abiraterone acetate and prednisolone (herein referred to as abiraterone acetate) (n = 9), abiraterone acetate and docetaxel (n = 1), enzalutamide alone (n = 9), abiraterone acetate and enzalutamide (n = 2), darolutamide alone (n = 1), darolutamide and docetaxel (n = 1), and apalutamide alone (n = 2) were studied. Of the 24 eligible studies, 18 reported CV events (75%): only 16 reported grade 3 or higher CV events (67%).…”
Section: Resultsmentioning
confidence: 99%
“…There were 22 studies that underwent full-text review, of which 10 studies were excluded, as specified in Figure 1. Details of the 12 studies comprising 13 524 participants included in our systematic review and their reported relevant toxic effects are summarized in the Table [21][22][23][24][25][26][27][28][29][30][31][32] and in eTable 1 in Supplement 1. All studies were multinational, with data collection ranging from 2008 to 2021.…”
Section: Search Resultsmentioning
confidence: 99%